‘Just about coping’: precarity and resilience among applied theatre and community arts workers in Northern Ireland - Jennings, Matt; Beirne, Martin; Knight, Stephanie (Irish Journal of Arts Management and Cultural Policy, 2017)
Through a focused study on the 2013 UK City of Culture programme in Derry / Londonderry, this paper explores the economic precarity of community-based artists, despite such programmes heavy reliance on such artists for proposed ‘success’. In March 2015, the Arts Council of Northern Ireland (ACNI) cut grant funding to some arts organisations by 40-100%, in order to manage an 11% reduction from the Northern Ireland Executive (NIE) in its 2015/16 Budget (ACNI, 2015). This was despite a high-profile ‘13p for the arts’ ACNI campaign, which had lobbied the NIE to preserve existing levels of arts funding (estimated at 13p per capita per week), already significantly lower than in other parts of the UK (‘far less than the 32 pence per week spent in Wales’, Litvack, 2014, online). Alongside cuts to spending on Social Development, Health and Education, and a reduction in European Union Peace funding, these have reduced the financial support available to applied theatre and community arts practitioners in Northern Ireland, despite such initiatives as the 2013 UK City of Culture programme. In these increasingly precarious conditions, how can community-based artists survive?